SAT0290 Higher Prevalence of Cardiovascular Risk Factors Among Patients with Psoriatic Arthritis. (23rd January 2014) - Hoff, M.; Gulati, A. M.; Kavanaugh, A.; Romundstad, P.; Haugeberg, G.
Abstract : Background: Studies have found that patients with PsA have an increased risk of cardiovascular disease (CVD). However, it is not clear to what extent this relates to intrinsic aspects of the disease or a greater prevalence of traditional CVD[1]. Objectives: To evaluate risk factors for CVD among patients with PsA. Methods: The patients were recruited from HUNT 3, a population survey performed 2006-2008 in Nord-Trøndelag, a county in Norway. An invitation letter was mailed to all 94, 194 adult inhabitants (aged > 20). A total of 50, 806 (54%) answered questionnaires (Q1) as well as underwent a brief medical examination. Q1 included questions about psoriasis, RA and AS. Patients answering they suffer from psoriasis further answered a question if they had PsA. 1238 persons reported that 1)they suffered or 2)may suffer from PsA 3)they had RA and psoriasis or 4)AS and psoriasis. Hospital files from these persons were evaluated by a rheumatologist (MH) in order to validate the PsA diagnosis. The evaluation was based on joint involvement, serology, X-ray skin involvement, treatment and the CASPAR criteria were applied. Patients found to have PsA without fulfilling the Caspar criteria were evaluated by 2 rheumatologists (MH and GH). Controls were all participants in HUNT 3, excluding patients found to have another rheumatic disease when evaluating hospitals file (N=50, 556). T-test and Chi-Square test were performed for group comparison. Multivariate analysis adjusted for age and gender were performed by logistic regression (dichotomous outcome) or linear regression (continuous outcome). Results: 338 patients (0.67%) were found to have PsA. Mean age was 54 yrs, 57.4% were females and disease duration was 9.2 yr. 52.1% were current or previous users of MTX and 18.6% of anti-TNF therapy. 95.6 % fulfilled the Caspar criteria. Patients with PsA were found to have higher BMI (28.4 vs. 27.2), weight (83.0 vs. 79.2), waist circumference (96.9 cm vs. 93.5) and diastolic BP (75.1 vs. 73.4) than the general population. In addition the prevalence of cigarette smoking was higher (21.3% vs. 16.4 %) and the performance of physical activity less than the general population (51.2% PsA pts reported physical activity > 2 times a week vs. 56.5%). There were no differences regarding systolic BP. All observations remained significant also after adjusting for age and gender, Table 1 . There were no differences related to age (54.3 vs. 53.9 yrs, p=0.58) and gender (female: 57.4% vs. 54.6 %, p=0.31). Conclusions: Patients with PsA have a greater prevalence of risk factors for CVD than the general population. This not only contributes to the greater prevalence of CVD in PsA, but also indicates that lifestyle changes should be emphasized as part of the treatment strategy for PsA patients. References: Johnsson H et al. ARD2012;71(4):480. Disclosure of Interest: M. Hoff: None Declared, A. Gulati: None Declared, A. Kavanaugh : None Declared, P. Romundstad: None Declared, G. Haugeberg Grant/research support from: Unrestricted research grant from Pfizer